Environmental Education: Concepts and Approaches for Degree of Students of the Federal University Fluminense - Souza, Vanessa Marcondes de (2011)
Modern society and its way of life resulted in an environmental crisis, and environmental education emerges as one of the tools to contribute to build a new model of society. As proposed in the National Curriculum Parameters (PCN), the environment is a crosscutting theme and, therefore, Environmental Education must be present in all learning spaces. This work intends to make a critical assessment of the perceptions and theoretical concepts and practices of environmental education by undergraduate students in Biology, Physical Education, Physics, Geography, History, Literature, Mathematics, Pedagogy and Chemistry Education from Fluminense Federal University. The responses of these students to a semi-open questionnaire were analyzed qualitatively and quantitatively. In the statements, naturalistic and anthropocentric views predominated. A contextualized view of the environment was more evident in the courses of Biology and Geography, which were considered to produce the most suitable professionals as environmental educators. Students from other courses feel very distant from environmental issues.The analyzed students showed ignorance, fragmentation and lack of discussion on environmental education. Thus, it is necessary to insert lectures on environmental education in all the undergraduate courses of Fluminense Federal University.